Prodrug strategies of antiviral nucleotides: Studies on enzymatically and thermally removable phosphate protecting groups - Leisvuori, Anna (fi=Turun yliopisto|en=University of Turku|, 2015)
Antiviral nucleosides are compounds that are used against viruses, such as human immunodeficiency virus (HIV) and hepatitis C virus (HCV). To act as therapeutic agent, the antiviral nucleoside needs to be phosphorylated to nucleotide in the body in three consecutive phosphorylation steps by cellular or viral enzymes. The first phosphorylation to the nucleoside monophosphate is often inefficient and leads to poor antiviral activity. The antiviral efficacy can be improved by applying a prodrug strategy and delivering the antiviral nucleoside directly as its monophosphate. In prodrug strategies of antiviral nucleotides, the negative charges on the phosphate moiety are temporarily masked with protecting groups. Once inside the cell, the protecting groups are removed by enzymatic or chemical processes. Many prodrug strategies apply biodegradable protecting groups, the removal of which is triggered by esterase enzymes. Several studies have, however, demonstrated that the removal rate of the second and subsequent esterase labile protecting groups significantly slows down after the first protecting group is removed due to the negative charge on the phosphodiester intermediate, which disturbs the catalytic site of the enzyme. In this thesis, esterase labile protecting group strategies where the issue of retardation could be avoided were studied. Prodrug candidates of antiviral nucleotides were synthesized and kinetic studies on the chemical and enzymatic stability were carried out. In the synthesized compounds, the second protecting group is cleaved from the monophosphate some other mechanism than esterase triggered activation or the structure of prodrug requires only one protecting group. In addition, esterase labile protecting group which is additionally thermally removable was studied. This protecting group was cleaved from oligomeric phosphodiesters both enzymatically and thermally and seems most attractive of the studied phosphate protecting groups. However, the rate of the thermal removal still is too slow to allow efficient protection of longer oligonucleotides and needs optimization. Key words: antiviral, nucleotide, prodrug, protecting group, biodegradable

Antiviraaliset nukleosidit ovat yhdisteitä, joita voidaan käyttää esimerkiksi HI-virusta (human immunodeficiency virus) ja hepatiitti C virusta vastaan. Jotta antiviraalinen nukleosidi voi toimia lääkeaineena, se on fosforyloitavaelimistössä nukleotidiksi viruksen tai solun entsyymien avulla kolmessa peräkkäisessä fosforylointireaktiossa. Ensimmäinen fosforylointireaktio nukleosidimonofosfaatiksi on kuitenkin usein tehoton ja johtaa heikkoon antiviraaliseen aktiivisuuteen. Antiviraalista vaikutusta voidaan tehostaa käyttämällä aihiolääkestrategiaa ja annostelemalla antiviraalinen nukleosidi suoraan monofosfaattina. Antiviraalisten nukleotidien aihiolääkestrategioissa fosfaatin negatiiviset varaukset naamioidaan suojaryhmillä, jotka irtoavat solun sisällä entsymaattisten tai kemiallisten prosessien avulla. Monissa suojaryhmästrategioissa käytetään biohajoavia suojaryhmiä, joiden irtoaminen tapahtuu esteraasientsyymien avulla. Useat tutkimukset ovat kuitenkin osoittaneet, että ensimmäisen suojaryhmän irrottua seuraavien suojaryhmien irtoaminen hidastuu merkittävästi johtuen fosfodiesterivälituotteen negatiivisesta varauksesta, joka häiritsee entsyymin katalyyttistä keskusta. Tässä väitöskirjassa tutkittiin esteraasien avulla irtoavia suojaryhmästrategioita, joissa suojaryhmien irtoamisen hidastuminen voitaisiin välttää. Työssä valmistettiin antiviraalisten nukleotidien aihiolääke-ehdokkaita ja tutkittiin niiden suojaryhmien entsymaattisen ja kemiallisen irtoamisen kinetiikkaa. Valmistetuissa yhdisteissä toinen monofosfaatin suojaryhmistä irtoaa jollain muulla kuin esteraasin aktivoimalla mekanismilla tai yhdisteen rakenne vaatii ainoastaan yhden suojaryhmän. Lisäksi tutkittiin esteraasin avulla irtoavaa suojaryhmää, joka irtoaa myös lämpötilan vaikutuksesta. Tämä suojaryhmä irtosi oligomeerisista fosfodiestereistä niin entsymaattisesti kuin lämpötilan vaikutuksestakin ja oli tutkituista fosfaatin suojaryhmistä lupaavin. Lämpötilan aiheuttama suojaryhmän irtoaminen on kuitenkin liian hidas ja vaatii optimointia, jotta sitä voitaisiin käyttää pidempien oligonukleotidien suojaamiseen. Asiasanat: antiviraalinen, nukleotidi, aihiolääke, suojaryhmä, biohajoava